Sex-Role Attitudes and Differing Lifestyles of Professional Married Women - Schmidt, L. L. (Canadian Journal of Counselling and Psychotherapy, 2012)
In view of the current interest in social attitudes towards sex roles, this research was undertaken (1) to survey professionally-trained married women regarding current sex-role attitudes and preferences, selected biographical data, and life-style choice; and (2) to determine relationships and/or differences existing among these variables and other psychological test data. The Sex-Role Inventory (Schmidt, 1972) established itself as a valid instrument in differentiating the traditional and libera-tionist groups, as well as among groups with differing life-styles, sex-role attitudes and preferences, and levels of cognitive dissonance. The EPPS and Study of Values also differentiated among the groups.